2022
DOI: 10.3390/cancers14030612
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Vincristine-Induced Peripheral Neuropathy in Children with Cancer: A Systematic Review and Meta-Analysis

Abstract: Vincristine-induced peripheral neuropathy (VIPN) is a debilitating side-effect of vincristine. It remains a challenge to predict which patients will suffer from VIPN. Pharmacogenomics may explain an individuals’ susceptibility to side-effects. In this systematic review and meta-analysis, we describe the influence of pharmacogenomic parameters on the development of VIPN in children with cancer. PubMed, Embase and Web of Science were searched. In total, 1597 records were identified and 21 studies were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The relation between sex and VIPN remains unclear [ 2 ]. Moreover, it was shown that ancestry is associated with VIPN development, with studies showing that Caucasian children are more often affected than African(-American) children [ 10 , 11 ]. It was thus hypothesized that genomic factors are associated with VIPN [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The relation between sex and VIPN remains unclear [ 2 ]. Moreover, it was shown that ancestry is associated with VIPN development, with studies showing that Caucasian children are more often affected than African(-American) children [ 10 , 11 ]. It was thus hypothesized that genomic factors are associated with VIPN [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that ancestry is associated with VIPN development, with studies showing that Caucasian children are more often affected than African(-American) children [ 10 , 11 ]. It was thus hypothesized that genomic factors are associated with VIPN [ 11 ]. Initially, this research focused on genomic differences between the CYP3A4 and CYP3A5 enzymes, since there was an ancestry dependent difference in the distribution of protein expression (i.e., African-American children express more CYP3A5 and Caucasian children express more CYP3A4).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations